China's competition and the export price strategies of developed countries - Giorgia Giovannetti; Marco Sanfilippo (FIW - Research Centre International Economics, 2012)
This paper analyzes the impact of Chinese competition on developed countries export prices, with a focus on Italy. After a theoretical discussion of the channels affecting export prices in presence of competitors from low income countries, we estimate the pricing behavior of two major manufacturing sectors, consumer goods and machinery, distinguishing destination markets according to their income level. Results show that export competition from China has affected Italian price strategies over the period 2000-08, in an idiosyncratic way according to the income level of importers, sector and technology level of products exported. Contrary to what observed for other high-income countries, we find that Italy has followed a very specific strategy to face Chinese competition. Instead of changing between sector, moving up to the technology ladder, Italy has kept its specialization in traditional sectors and has upgraded the quality of its low-tech and laborintensive products, when in direct competition with Chinese ones. For higher technology products, on the other hand, it has adjusted prices downward to reduce Chinese competitive pressure, especially in segments where it does not hold a comparative advantage, while it has fostered differentiation only for some niche products within the sectors with higher specialization.
Keywords: F10; F14; 330; China; export price competition; Italy